The Dynamic Roles of the Inner Membrane Complex in the Multiple Stages of the Malaria Parasite - Ferreira, Josie Liane; Heincke, Dorothee; Wichers, Jan Stephan; Liffner, Benjamin; Wilson, Danny W.; Gilberger, Tim-Wolf (Frontiers in Cellular and Infection Microbiology, 2021)
Apicomplexan parasites, such as human malaria parasites, have complex lifecycles encompassing multiple and diverse environmental niches. Invading, replicating and escaping from different cell types, along with exploiting each intracellular niche, necessitates large and dynamic changes in parasite morphology and cellular architecture. The inner membrane complex (IMC) is a unique structural element that is intricately involved with these distinct morphological changes. The IMC is a double membrane organelle that forms de novo and is located beneath the plasma membrane of these single-celled organisms. In Plasmodium spp. parasites it has three major purposes: it confers stability and shape to the cell, functions as an important scaffolding compartment during the formation of daughter cells, and plays a major role in motility and invasion. Recent years have revealed greater insights into the architecture, protein composition and function of the IMC. Here, we discuss the multiple roles of the IMC in each parasite lifecycle stage as well as insights into its sub-compartmentalization, biogenesis, disassembly and regulation during stage conversion of P. falciparum.